Community Service in the Suitable Utilization of Tourism Space in Seminyak Village, Badung District, Bali - Ayyada, Muhammad Arya Feyza; Kartika, Ninda; Nugraha, Ferry; Nugroho, Fachrizal Gusti; Karim, Muh Husain Abdul; Yahya, Sofy Alaydhiya; Pamungkas, Harry Duta Jiwangga; Hokkydia, Puspita Ayu Tsalsa; Santi, Eny Maya; Hidayatullah, Muhammad Lecha Faroq; Jafis, Muhammad; Kurniawati, Amanda Oktavia; Sari, Dewi Novita (Journal of Community Services and Engagement: Voice of Community (VOC), 2024)
The increase in the number of tourist attractions from year to year is increasingly irregular, so the need for supporting facilities also increases. As a result, the Seminyak Village Community built tourism support facilities such as hotels and villas in a spatial plan that was not intended for them. Another factor in the inappropriate use of tourism space is people's ignorance regarding spatial planning. The Badung Regency Government has not yet carried out socialization regarding spatial planning to the village or sub-district level. The aim of this research is to analyze the use of tourism space in Seminyak Village and provide recommendations for the suitability of space use. The results of this research are that there is a mismatch in the use of tourism space in Seminyak Village which is intended for the construction of hotels and villas